2020
DOI: 10.1177/0098628320979893
|View full text |Cite
|
Sign up to set email alerts
|

Intended and Actual Changes in Study Behaviors in an Introductory and Upper-Level Psychology Course

Abstract: We examined self-directed studying of students in an introductory (Study 1) and upper-level (Study 2) psychology course. Students reported their study behaviors for Exam 1 and 2, and wrote Exam 2 study plans. In both studies, students planned to and ultimately did use more active strategies for Exam 2 than Exam 1. However, they struggled to follow through on plans to space studying over time. In Study 1, we also found that greater use of active strategies (e.g., retrieval practice) was associated with higher e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Relative to the healthy habits condition, students in the study habits condition increased the use of active strategies relative to passive strategies and were slightly less distracted while studying. In addition, greater active strategy use was associated with higher exam performance, which is consistent with prior findings from similar studies (Brown-Kramer, 2022; Rowell et al, 2021; Walck-Shannon et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Relative to the healthy habits condition, students in the study habits condition increased the use of active strategies relative to passive strategies and were slightly less distracted while studying. In addition, greater active strategy use was associated with higher exam performance, which is consistent with prior findings from similar studies (Brown-Kramer, 2022; Rowell et al, 2021; Walck-Shannon et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, spacing out study sessions is important for long-term retention (Cepeda et al, 2008; Dunlosky et al, 2013). Yet, some students still report spending a large portion of study time in less effective ways (Blasiman et al, 2017; Ekuni et al, 2022; Hartwig & Dunlosky, 2012; Karpicke et al, 2009; Rowell et al, 2021). There are several possible reasons for this from cognitive and motivational standpoints (see Bjork et al, 2013; Zepeda et al, 2020, for reviews), including that students do not know about effective strategies, believe that less effective strategies are more effective (Blasiman et al, 2017; McCabe, 2011), plan to use effective strategies too late (Kuhbandner & Emmerdinger, 2019), or intend to use effective strategies but fail to follow-through (Blasiman et al, 2017; Morehead et al, 2016; Susser & McCabe, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studying for an exam one day earlier may not seem like a particularly meaningful result, but given that students began studying for the first exam less than four days before that exam, this difference reflects a more than 30% increase for the second exam. Further, getting students to use more spaced practice, which is what this change suggests, has been one of, if not the most difficult challenges identified in the literature (Brown-Kramer 2021;Brown-Kramer 2022;Dunlosky and O'Brien 2020;McCabe et al 2021;Rowell, Frey, and Walk-Shannon 2021). This also importantly extends the work from Maurer and Shipp's (2021) investigation, because although they collected data about total days studying and when students started studying, they dropped it from analyses because of insufficient statistical power.…”
Section: Discussionmentioning
confidence: 76%
“…Prior literature has documented that simply educating students about the benefits of more effective study methods to correct their misperceptions is insufficient to change their behavior and that scaffolding on how to use the methods and repeated opportunities to practice them are required (Dunlosky and O'Brien 2020;Dunlosky and Rawson 2015;Rodriguez et al 2018). Multiple recent assessments of interventions that simultaneously focused on both retrieval practice and spaced practice have consistently shown that despite the method of intervention, students are more likely to adopt retrieval practice methods than spaced practice methods (Brown-Kramer 2021;Brown-Kramer 2022;McCabe et al 2021;Rowell, Frey, and Walk-Shannon 2021). Difficulties with time management have been identified by students as a major barrier to using high-utility strategies in general (Beattie, Laliberté, and Oreopoulos 2018;Biwer et al 2020;Blasiman, Dunlosky, and Rawson 2017).…”
Section: Introductionmentioning
confidence: 99%